Influence of Arbuscular Mycorrhizal Fungi on Nitrogen Dynamics During Cinnamomum camphora Litter Decomposition - Yuehong Gao; Xiaoyu Long; Yiqi Liao; Yonghui Lin; Zaihua He; Qin Kong; Xiangshi Kong; Xingbing He (Microorganisms)
Arbuscular mycorrhizal fungi (AMF) can preferentially absorb the released ammonium (NH4+) over nitrate (NO3−) during litter decomposition. However, the impact of AMF’s absorption of NH4+ on litter nitrogen (N) decomposition is still unclear. In this study, we investigated the effects of AMF uptake for NH4+ on litter N metabolic characteristics by enriching NH4+ via AMF suppression and nitrification inhibition in a subtropical Cinnamomum camphora forest. The results showed that AMF suppression and nitrification inhibition significantly decelerated litter decomposition in the early stage due to the repression of NH4+ in extracellular enzyme activity. In the late stage, when soil NH4+ content was low, in contrast, they promoted litter decomposition by increasing the extracellular enzyme activities. Nitrification inhibition mainly promoted the utilization of plant-derived N by promoting the degradation of the amide I, amide II, and III bands by increasing protease activity, and it promoted ammonification by increasing urease activities, whereas it reduced the utilization of microbial-derived N by decreasing chitinase activity. On the contrary, AMF suppression, which significantly reduced the ammonification rate and increased the nitrification rate, only facilitated the degradation of the amide II band. Moreover, it intensified the microbial-derived N decomposition by increasing chitinase activity. The degradation of the amide I and II bands still relied on the priming effects of AMF on soil saprotrophs. This was likely driven by AMF-mediated phosphorus (P) mineralization. Nutrient acquiring, especially P by phosphatase, were the main factors in predicting litter decomposition and protein degradation. Thus, AMF could relieve the end-product repression of locally enriched NH4+ in extracellular enzyme activity and promote early-stage litter decomposition. However, the promotive effects of AMF on litter protein degradation and NH4+ release rely on P mineralization. Our results demonstrated that AMF could alleviate the N limitation for net primary production via accelerating litter N decomposition and reducing N loss. Moreover, they could restrict the decomposition of recalcitrant components by competing with saprotrophs for nutrients. Both pathways will contribute to C sequestration in forest ecosystems, which advances our understanding of AMF’s contribution to nutrient cycling and ecosystem processes in subtropical forests.